-4x+2/6=7

Simple and best practice solution for -4x+2/6=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+2/6=7 equation:



-4x+2/6=7
We move all terms to the left:
-4x+2/6-(7)=0
determiningTheFunctionDomain -4x-7+2/6=0
We multiply all the terms by the denominator
-4x*6+2-7*6=0
We add all the numbers together, and all the variables
-4x*6-40=0
Wy multiply elements
-24x-40=0
We move all terms containing x to the left, all other terms to the right
-24x=40
x=40/-24
x=-1+2/3

See similar equations:

| 2(4a-9)+3=5a-1 | | 10x-8x+12=-6 | | x=18+0.4/0.4 | | 6(3+a)=+6a | | 4x+3x+90=221 | | 5(y+3)=+15 | | 7x-5=5x+2 | | y+10/8=y+4/6 | | 1000=50x+160 | | 81=42+x | | p^2-9=10 | | -0.6x+9.39=-0.2x+1.79 | | -0.5=-5/18x | | ​$4.1​​4​​=​3​​x​​ | | -16x^2+32x+180=0 | | ​$4.41​​4​​=​3​​x​​ | | 1.6k=31/5 | | 0.4(5x−15)=2.5(x+3) | | 10/x=0.1 | | (z-4)^2+25=0 | | 2x-6x-x=-1 | | 7.1x+9-8.1x=1 | | 3y=84/147 | | 5+(x/6)=-9 | | 5x-6(x+2)=14 | | 6(3-x=-4(2x-1) | | 1476=9(12x-40) | | 6x+2=(5x-27)+(3x+1) | | -4x/5-2=18 | | -299=-4x+7(7x+28) | | X^2(x+3)(x+3)=0 | | 38x=74 |

Equations solver categories